Fabry disease: twenty novel alpha-galactosidase A mutations and genotype-phenotype correlations in classical and variant phenotypes. - Germain, Dominique P. (2002)
BACKGROUND: Fabry disease (OMIM 301500) is an X-linked inborn error of glycosphingolipid metabolism resulting from mutations in the alpha-galactosidase A (alpha-Gal A) gene. The disease is phenotypically heterogeneous with classic and variant phenotypes. To assess the molecular heterogeneity, define genotype/phenotype correlations, and for precise carrier identification, the nature of the molecular lesions in the alpha-Gal A gene was determined in 40 unrelated families with Fabry disease. MATERIALS AND METHODS: Genomic DNA was isolated from affected males or obligate carrier females and the entire alpha-Gal A coding region and flanking sequences were amplified by PCR and analyzed by automated sequencing. Haplotype analyses were performed with polymorphisms within and flanking the alpha-Gal A gene. RESULTS: Twenty new mutations were identified (G43R, R49G, M72I, G138E, W236X, L243F, W245X, S247C, D266E, W287C, S297C, N355K, E358G, P409S, g1237del15, g10274insG, g10679insG, g10702delA, g11018insA, g11185-delT), each in a single family. In the remaining 20 Fabry families, 18 previously reported mutations were detected (R49P, D92N, C94Y, R112C [two families], F113S, W162X, G183D, R220X, R227X, R227Q, Q250X, R301X, R301Q, G328R, R342Q, E358K, P409A, g10208delAA [two families]). Haplotype analyses indicated that the families with the R112C or g10208delAA mutations were not related. The proband with the D266E lesion had a severe classic phenotype, having developed renal failure at 15 years. In contrast, the patient with the S247C mutation had a variant phenotype, lacking the classic manifestations and having mild renal involvement at 64 years. CONCLUSIONS: These results further define the heterogeneity of alpha-Gal A mutations causing Fabry disease, permit precise heterozygote detection and prenatal diagnosis in these families, and provide additional genotype/phenotype correlations in this lysosomal storage disease.